Service Quality for Regional Drinking Water Company (PDAM) Sidoarjo Regency: Kualitas Pelayanan Perusahaan Daerah Air Minum (PDAM) Kabupaten Sidoarjo - Rostania, Cici Mei Nur; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2021)
Stipulated in the 1945 Constitution, the implementation of public services in Indonesia is an effort to fulfill the basic needs and rights of every citizen. In fact, efforts to provide public services have not run optimally, especially in agencies that provide public services. One of them is the provision of clean water services at the Waru II Branch of Drinking Water Company, Sidoarjo Regency. The purpose of the study was to measure the quality of service at the Regional Drinking Water Company (PDAM)